1996
DOI: 10.1111/j.1476-5381.1996.tb15596.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclopiazonic acid and ryanodine on cytosolic calcium and contraction in vascular smooth muscle

Abstract: 1 In smooth muscle, both Ca2+ release from the sarcoplasmic reticulum (SR) and Ca2+ influx across the plasma membrane are responsible for the increase in the cytosolic Ca2+ level ([Ca2+]j). To understand further the role of SR on smooth muscle contraction, the effects of an inhibitor of the SR Ca2+ pump, cyclopiazonic acid (CPA 10 gM), an inhibitor of the Ca2+-induced Ca2+ release, ryanodine, (10 gM), and an activator of the Ca2'-induced Ca2+ release, caffeine (20 mM), on [Ca2+]i and contractile force were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 19 publications
(26 reference statements)
3
21
0
Order By: Relevance
“…In canine trachea, it has been demonstrated that isoproterenol inhibits CCh-stimulated [Ca2+] i, support ing the first possibility (Gunst and Bandyopadhyay, 1989;Ozaki et al, 1990a). However, it was also demonstrated that FK and isoproterenol inhibit high K+-induced contraction without decreasing [Ca2+] i in tracheal smooth muscle (Ozaki et al, 1990a;Tang et al, 1992), as is the case with vascular smooth muscle (Abe and Karaki, 1989;Ushio-Fukai et al, 1993). In bovine tracheal smooth muscle stimulated with carbachol (CCh), it has been reported that isoproter enol decreased MLC phosphorylation and force of contraction in parallel (Tang et al, 1992;Stull et al, 1990).…”
Section: Introductionmentioning
confidence: 84%
“…In canine trachea, it has been demonstrated that isoproterenol inhibits CCh-stimulated [Ca2+] i, support ing the first possibility (Gunst and Bandyopadhyay, 1989;Ozaki et al, 1990a). However, it was also demonstrated that FK and isoproterenol inhibit high K+-induced contraction without decreasing [Ca2+] i in tracheal smooth muscle (Ozaki et al, 1990a;Tang et al, 1992), as is the case with vascular smooth muscle (Abe and Karaki, 1989;Ushio-Fukai et al, 1993). In bovine tracheal smooth muscle stimulated with carbachol (CCh), it has been reported that isoproter enol decreased MLC phosphorylation and force of contraction in parallel (Tang et al, 1992;Stull et al, 1990).…”
Section: Introductionmentioning
confidence: 84%
“…The Ca 2+ released from SR seems to be mainly contributed to initial phasic contraction, while the Ca 2+ that enters through voltage-dependent Ca 2+ channels and/or Ca 2+ -permeable non-selective cation channels on the cell membrane contributes to later tonic contraction [17][18][19] . In the present study, 100 µmol/L doxorubicin was shown to induce both phasic and tonic contractions in the denuded vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The data from previous studies indicate that the effects of ryanodine on vessel contraction and transient [Ca 2+ ] i are determined by at least three factors, ie, the type of vessel, the basal tension of the vessel, and the concentration of ryanodine. Significant ryanodineinduced vessel contraction and/or increase in transient [Ca 2+ ] i have been observed in dog cerebral arteries with basal tone at 1-100 µmol/L [20] , in fetal rabbit distal (but not proximal) pulmonary artery smooth muscle cells at 50 µmol/L [21] , and in rat femoral arteries at 30 nmol/L−30 µmol/L [22] ; the absence of an effect of ryanodine on vessel contraction and/or transient [Ca 2+ ] i has been shown in the ferret portal vein at a dose of 10 µmol/L [17] , in the aorta of C57BL/6 mice at 10 µmol/L [10] , and in rat aortas at 10 µmol/L [23] . Therefore, one should be very cautious to compare the effects of ryanodine on the vasomotion and/or transient [Ca 2+ ] i of cells and to explain the interaction between ryanodine and other inhibitors of RyRs in different vascular smooth muscles.…”
Section: Wwwchinapharcom Shen B Et Almentioning
confidence: 97%
“…Elevation of basal calcium level, increased net calcium in¯ux, and slowed cellular extrusion of calcium ions are some of the main ®ndings in muscle treated with Ry, SR Ca 2+ pump inhibitors, or caeine, which at high doses also acts to release Ca 2+ via Ry receptors (Chen & van Breemen, 1992;Abe et al, 1996).…”
Section: Introductionmentioning
confidence: 99%